The non-euphoric phytocannabinoid cannabidivarin counteracts intestinal inflammation in mice and cytokine expression in biopsies from UC pediatric patients. (November 2019) - Pagano, E.; Romano, B.; Iannotti, F.A.; Parisi, O.A.; D'Armiento, M.; Pignatiello, S.; Coretti, L.; Lucafò, M.; Venneri, T.; Stocco, G.; Lembo, F.; Orlando, P.; et al.
Graphical abstract: Abstract: Patients with ulcerative colitis (UC) using marijuana have been reported to experience symptomatic benefit. Cannabidivarin (CBDV) is a safe non-psychoactive phytocannabinoid able to activate and desensitize TRPA1, a member of the TRP channels superfamily, which plays a pivotal role in intestinal inflammation. Here, we have investigated the potential intestinal anti-inflammatory effect of CBDV in mice and in biopsies from pediatric patients with active UC. Colonic inflammation was induced in mice by dinitrobenzenesulfonic acid (DNBS). The effect of orally administered CBDV on macroscopic and microscopic damage, inflammatory parameters ( i.e . myeloperoxidase activity, intestinal permeability and cytokine production) and faecal microbiota composition, was evaluated 3 days after DNBS administration. TRPA1 expression was studied by RT-PCR in inflamed colons of mice as well as in mucosal colonic biopsies of children with active UC, whose response to incubation with CBDV was also investigated. CBDV attenuates, in a TRPA1-antagonist sensitive manner, DNBS-induced signs of inflammation including neutrophil infiltration, intestinal permeability, and cytokine ( i.e . IL-1β, IL-6 and the chemokine MCP-1) production. CBDV also alters the dysregulation of gut microbiota associated to colitis. Finally, CBDV lessens cytokine expression in colonic biopsies from pediatric patients with ulcerative colitis, a condition in which TRPA1 was up-regulated. Our preclinical study shows that CBDV exerts intestinal anti-inflammatory effects in mice via TRPA1, and in children with active UC. Since CBDV has a favorable safety profile in humans, it may be considered for possible clinical trials in patients with UC.